DEVELOPMENT AND VALIDATION OF SPECTROPHOTOMETRIC METHODS FOR SIMULTANEOUS ESTIMATION OF VILANTEROL AND FLUTICASONE FUROATE IN PHARMACEUTICAL FORMULATIONS - Masimukku, Siva Kishore; Chintal, Rambabu (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective:Â To develop a simple, rapid,Â precise, accurate, sensitive spectrophotometric methods (A&B) were developed for simultaneous estimation and validation of Vilanterol (VTL) and Fluticasone Furoate (FFE) in pure and tablet dosage forms. Method:Â Â Method A is a simultaneous equation method and method B is a first order derivative spectrophotometric method. Pure drug samples of VTL and FFE were dissolved in a mixture of Methanol and Ethanol in the ratio of 1:1 (v/v) and foundÂ toÂ haveÂ absorbanceÂ maximaÂ atÂ 231nm for VTL andÂ 260nm for FFE respectively Results:Â The linearity lies between 2.5â€“10Âµg/ml for VTL and 10â€“60Âµg/ml for FFE in these two methods (A&B).Â The correlation coefficient (r2) was found to be 0.999 for both VTL and FFE, the limit of detection and limit of quantification were found to be 0.015Âµg/ml and 0.05Âµg/ml for VTL and 0.05Âµg/ml and 0.2Âµg/ml for FFE respectively. The results of analysis have been validated statistically by recovery studies as per ICH guidelines. Conclusion: The two methods A&B showed good reproducibility and recovery with % RSD less than 2.Â Hence both methods were found to be rapid, specific, precise and accurate and can be successfully applied for the routine analysis of VTL and FFE in pure and combined dosage form. Keywords: Fluticasone furoate, Vilanterol, Derivative spectrophotometric, Simultaneous equation method, Method development and validation.